Smoldering (asymptomatic) multiple myeloma: Current diagnostic criteria, new predictors of outcome, and follow-up recommendations - Bladé, J.; Dimopoulos, M.; Rosiñol, L.; Rajkumar, S.V.; Kyle, R.A. (Journal of Clinical Oncology, 2010)
Purpose: To provide an overview on smoldering (asymptomatic) multiple myeloma (SMM) including current diagnostic criteria, predictors of progression, pattern of progression, and outcome. Design: A comprehensive review of the literature on risk factors for progression, treatment attempts to delay progression and outcome in patients with SMM. Results: The risk factors for progression of SMM include: plasma cell mass including M-protein size and percentage of bone marrow clonal plasma cells (BMPC), abnormal free light chain ratio, proportion of phenotypically abnormal BMPC, immunoparesis, evolution pattern (evolving v nonevolving), and pattern of magnetic resonance imaging abnormalities. Most patients with SMM progress with anemia and/or skeletal involvement. Immediate therapy with cytotoxic agents, such as melphalan/prednisone has not resulted in improved outcome. Patients should not be treated until progressive disease with end-organ damage occurs. Increasing anemia is the most reliable indicator of progression. Conclusion: These recently recognized predictors of outcome may be helpful for better disease monitoring and for investigation of new treatment approaches. Thus, recommendations for follow-up every to 3 to 6 months depending on the risk of progression are suggested, and clinical trials with new noncytotoxic biologically derived agents to delay progression, particularly in high-risk patients, are ongoing. © 2009 by American Society of Clinical Oncology.